Law Enforcement of the Financial Services Authority against Customer Rights on Fraudulent Promissory Notes Issued by Non-Bank Financial Institutions - Ira Kharisma; Lilik Mulyadi; Joko Sriwidodo (International Journal of Science and Society, 2023)
The development of the economy in Indonesia requires large funds so that it is necessary to provide facilities for the provision of funds needed by the community, so that the creation of financial institutions, one of which is a non-bank financial institution. Non-Bank Financial Institutions are business entities in the financial sector that are allowed to collect and distribute funds to the public but not in the form of savings, demand deposits or time deposits. Promissory Notes are commercial securities that are regulated by law, in this case a non-bank financial institution that issues promissory notes as a means of transaction must obtain permission from financial institutions, namely the Financial Services Authority and Bank Indonesia. Based on the background of the problems above that have been explained, the issue that will be raised is how is Law Enforcement from the Financial Services Authority against fraudulent promissory note customers from Non-Bank Financial Institutions that do not have a license. The method used is normative juridical which is carried out to obtain the necessary legal materials related to the object of research. The results of this study are based on the Financial Services Authority Regulation Number 35/POJK.05/2018 concerning Conducting a Financing Company Business spurring the growth of the performance of the financing industry which is considered not optimal.